Comparative study of mini chromosome maintenance deficient-5 and urine cytology as urinary biomarkers for the diagnosis of bladder cancer - Onwuasoanya, Uzodimma E.; Mungadi, Ismaila A.; Agwu, Ngwobia P.; Ahmed, Abdullahi A.; Ndodo, Emeka (International Surgery Journal, 2025)
Background: Bladder cancer is the 9th most common cancer worldwide and the 13th most common cause of death accounting for 145,000 deaths worldwide. In Sokoto, Nigeria, bladder cancer is the most common male cancer and the area is endemic for schistosomal infestation. Mini chromosome maintenance deficient 5 (MCM5) is a potential urinary biomarker for bladder cancer diagnosis, study of this biomarker is essential to compare its effectiveness in diagnosing bladder cancer with voided urine cytology. Methods: Patients presenting at the urology out-patient clinic of the Usmanu Danfodiyo University Teaching Hospital, Sokoto between February 2,2018 and February 1, 2019 with clinical and radiological suspicion of bladder cancer who met the inclusion criteria and gave informed consent were recruited for the study. Data analysis was done using IBM statistical package for the social sciences (SPSS) version 20.0 computer software package and diagnostic validity indicators of each marker was computed. Results: A total of 65 patients were recruited into the study with a mean age of 51.9 years and standard deviation of ±14.7. The male to female ratio was 6:1. The commonest histological type of bladder cancer seen was squamous cell carcinoma (70.8%). The biomarker MCM5 was found to be more sensitive in diagnosing squamous cell carcinoma than the other histological types of bladders. Conclusion: The biomarker MCM5 is more sensitive but less specific than voided urine cytology in the diagnosis of bladder cancer. Also, MCM5 is more sensitive in diagnosing squamous cell carcinoma than other histological types of bladder cancer.